Effects of Growing Environment, Container Size and Potting Media on Seedling Characteristics of Gmelina arborea Roxb. - Jabeen, Shama; Lone, Raheel Anwar; Ginwal, H. S.; Tamta, Nidhi; Kaur, Jaspreet; Lukram, Daylahoya; Yadav, Amit (Indian Forester, 2023)
The study was carried out to find the effect of container size on the growth and quality of seedlings of Gmelina arborea. Observations were recorded at 60, 100 and 140 days on morphological, biomass and quality parameters after sowing. Among different container sizes, better plant height, collar diameter and tap root length at all intervals, maximum leaf number at 100 and 140 DAS resulted in seedlings raised in 17 Ã— 13 cm poly bags, followed by 300 cc root trainers. Maximum numbers of lateral roots were recorded in 300 cc root trainers. Similarly, 17 cm Ã— 13 cm poly bags were optimum for comparative biomass (fresh and dry) and seedling quality parameters, closely followed by 300 cc root trainers. The sturdiness and seedling quality have direct and positive relationship with container size and results revealed that container size had significant effect for most of the growth parameters.